METHODOLOGY OF FORECASTING THE INTEREST RATE OF THE EUROPEAN CENTRAL BANK IN SHORT-TERM OUTLOOK - Anastasiya V. Skuratova (Plekhanov Russian University of Economics, 2017)
The article deals with the issue of forecasting the dynamics of the interest rate of the European Central Bank as a central bank whose activity aims at supporting price stability and whose interest rate is an indicator showing the direction of monetary and credit policy. The author designed methodology, which allows business entities to use a simplified Tailor rule to forecast the dynamics of the interest rate of the European Central Bank in the short-term outlook (up to one year). The algorithm of forecasting was proposed, sources of initial data were provided, the comparison between the actual interest rate and the interest rate calculated by Tailor rater was made.